The Role of Mosque Istiqlal Osaka, Japan: Preliminary Observations on Islamic Religious Practices for the Indonesian Migrant Worker Society - Imron Natsir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research paper presents preliminary observations on the role of Mosque Istiqlal in Osaka, Japan, in facilitating Islamic religious practices for the Indonesian migrant worker society. As globalization has led to increased migration flows, many Indonesian workers have moved to Japan in search of better economic opportunities. However, living in a non-Muslim majority country presents challenges for practicing their faith. The study aims to investigate how Mosque Istiqlal serves as a religious and social hub for the Indonesian migrant worker community in Osaka. Through qualitative research methods including interviews, participant observations, and document analysis, this research explores the various functions of the mosque in supporting the religious needs and social integration of Indonesian migrants.The findings reveal that Mosque Istiqlal plays a crucial role in providing a space for collective worship, religious education, cultural events, and social support for the Indonesian migrant worker society. The mosque serves as a center for fostering a sense of community, preserving cultural identity, and offering a familiar environment for religious practices in a foreign land.Through this preliminary study, we highlight the significance of religious institutions like Mosque Istiqlal in supporting the well-being and integration of migrant communities in host countries. The research underscores the importance of further exploration into the role of religious institutions in facilitating the religious and social needs of migrant populations, contributing to a better understanding of the intersection between religion, migration, and community building.